2018
DOI: 10.1007/s10508-017-1121-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Body Image, Contraceptive Use, and Sexual Health Outcomes Among an Ethnically Diverse Sample of Women

Abstract: This cross-sectional study examined the links between body appreciation, contraceptive use, and sexual health outcomes. Body appreciation has been shown to influence contraceptive use in homogenous samples of women. However, a common problem in body image literature is a lack of racial and ethnic diversity with regard to sample; this study was able to take steps toward overcoming that limitation. A sample of 499 women aged 18-56 (M = 26.24; SD = 6.15) was recruited via Reddit.com-White (29.3%, n = 120), Asian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It was also strongly associated with feeling comfortable with one’s sexual desire and sexual agency through this desire, providing evidence that desire fully mediated the relationship between embodiment and sexual agency. Limited quantitative research has found connections between measures of body appreciation and sexual functioning (Ramseyer Winter et al, 2018; Satinsky et al, 2012), while a larger body of quantitative research has explored the associations of poor body image and self-objectification with decreased sexual safety and agentic behaviors (e.g., Manago et al, 2015; Ramsey & Hoyt, 2015). Our research provides distinctive quantitative evidence that embodiment is a key component of young women’s sexual subjectivity and well-being (Holland et al, 1998; Tolman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also strongly associated with feeling comfortable with one’s sexual desire and sexual agency through this desire, providing evidence that desire fully mediated the relationship between embodiment and sexual agency. Limited quantitative research has found connections between measures of body appreciation and sexual functioning (Ramseyer Winter et al, 2018; Satinsky et al, 2012), while a larger body of quantitative research has explored the associations of poor body image and self-objectification with decreased sexual safety and agentic behaviors (e.g., Manago et al, 2015; Ramsey & Hoyt, 2015). Our research provides distinctive quantitative evidence that embodiment is a key component of young women’s sexual subjectivity and well-being (Holland et al, 1998; Tolman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we tested the relations of embodiment, desire, and entitlement to pleasure to sexual agency in the services of pleasure and protection in a multivariate model (Figure 1). Given theory and research on agency as anchored in one’s embodied feelings and desires (i.e., Frie, 2008; Horne & Zimmer-Gembeck, 2006; Maxwell & Aggleton, 2012; Tolman, 2002), and associations between measures of embodiment, desire, entitlement to pleasure, and sexual agency in the quantitative literature (i.e., Horne & Zimmer-Gembeck, 2006; Ramseyer Winter et al, 2018), we predicted that embodiment would be associated with these two forms of sexual agency through sexual desire and entitlement to sexual pleasure. Specifically, we hypothesized:…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Female sexuality is related to quality of life and body image, and a woman’s perception of her own body is associated with sexual satisfaction [ 18 , 19 ]. Negative body image is linked to lower sexual activity, less satisfaction, poor communication and seeking professional help [ 20 ]. Women are a more vulnerable group because of society’s idealisation of their bodies.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of MO focuses on nutrition, physical exercise, lifestyle habits and surgical treatment. Bariatric surgery is an effective therapeutic measure for treatment of MO and its comorbidities, as it improves diabetes mellitus, dyslipidaemia and hypertension [ 11 ], as well as quality of life, sex hormones, fertility and sexual function [ 5 , 11 , 14 , 15 , 20 ]. Body perception and sex life are key factors in the decision to undergo bariatric surgery.…”
Section: Introductionmentioning
confidence: 99%